Molecular and Nanoaggregation in Cyclometalated Iridium(III) Complexes through Structural Modification. Issue 26 (16th August 2016) - Mukhopadhyay, Sujay; Singh, Roop Shikha; Biswas, Arnab; Maiti, Biswajit; Pandey, Daya Shankar
Abstract : New terpyridyl ligandsTP1, TP2 and cyclometalated iridium(III) complexes1 and2 based on these ligands have been synthesized. The ligands and complexes have been characterized by elemental analysis and spectroscopic studies (ESI‐MS, 1 H and 13 C NMR, UV/Vis, fluorescence). The molecular structure of1 has been verified by X‐ray single‐crystal analysis. It has been unambiguously established that variation of the substituents on1 and2 leads to molecular aggregation in1, while2 remains nonaggregated. Furthermore, complexes1 and2 have been successfully utilized as capping agents for the stabilization of gold nanoparticles (AuNPs). It is of note that1 forms discretely, while2 aggregates AuNPs through the assemblage of ultrasmall nanoparticles. It has been affirmed by 1 H NMR titration studies that – N H groups from1 and2 are involved in the capping of AuNPs. The role of simple structural variations in directing molecular and nanoaggregation has been clearly established for the first time by spectroscopic (UV/Vis, fluorescence, 1 H NMR titration) and morphological studies [SEM, TEM, EDX (energy‐dispersive X‐ray), DLS (dynamic light scattering)]. Abstract : The role of simple structural variations in directing molecular and nanoaggregation has been established for the first time in two new cyclometalated iridium(III) complexes with the help of various spectroscopic (UV/Vis, fluorescence, 1 H NMR titration) and morphological analyses [SEM, TEM, EDX (energy‐dispersive X‐ray), DLS (dynamic light scattering)].